Tunable bandpass filters based on π‐shifted mechanical long‐period fibre gratings in two‐mode fibres. Issue 11 (1st May 2015) - Sakata, H.; Komori, K.; Ono, Y.
Abstract : A phase‐shifted tunable long‐period fibre grating in which a passband can be tuned over a wide spectral range is presented. This device is operated with an electromagnet in combination with a coil spring that includes a shift ring inserted in the middle. The passband wavelength is changed between 1520 and 1630 nm by actuating the coil spring. The minimum transmittance of the rejection band is controlled down to −15 dB by turning on the electromagnet.